Evaluation of cytomegalovirus (CMV)‐specific t‐cell immunity for the assessment of the risk of active CMV infection in non‐immunosuppressed surgical and trauma intensive care unit patients. Issue 10 (19th July 2013) - Clari, María A.; Aguilar, Gerardo; Benet, Isabel; Belda, Javier; Giménez, Estela; Bravo, Dayana; Carbonell, José A.; Henao, Liliana; Navarro, David
ABSTRACT The current study was designed to assess the predictive value of the evaluation of cytomegalovirus (CMV)‐specific T‐cell immunity early following admission to the intensive care unit for inferring the risk of active CMV infection in non‐immunosuppressed surgical and trauma patients. A total of 31 CMV‐seropositive patients were included. Patients were screened for the presence of CMV DNA in plasma and in tracheal aspirates by real‐time PCR. Enumeration of CMV pp65 and IE‐1‐specific IFN‐γ CD8+ and CD4+ T cells was performed by flow cytometry for intracellular cytokine staining. Virological and immunological monitoring was conducted once or twice a week. Active CMV infection occurred in 17 out of 31 patients. Undetectable levels of pp65 and IE‐1‐specific IFN‐γ CD8+ and CD4+ T‐cell subsets cells were observed in 10 patients who developed active CMV infection and in one who did not (at a median of 2 days following ICU admission). Peak CMV DNA loads in both tracheal aspirates and plasma were substantially higher (P = 0.018 and P = 0.091, respectively) in patients with undetectable IFN‐γ T‐cell responses than in patients with detectable responses. The expansion of both CMV‐specific T‐cell subsets following detection of active CMV infection was demonstrated in 9 out of 14 patients with active CMV infection. In conclusion, the evaluation of CMV pp65 and IE‐1‐specific IFN‐γ‐producing CD8+ and CD4+ T cells early following ICU admission may allow the identification of patients most at risk of either having or developing an episode of active CMV infection, particularly those associated with high‐level virus replication. J Med. Virol. 85:1802–1810, 2013. © 2013 Wiley Periodicals, Inc.